2005
DOI: 10.1007/s00192-005-1324-3
|View full text |Cite
|
Sign up to set email alerts
|

The choice of elective cesarean delivery in obstetrics: a voluntary survey of Canadian health care professionals

Abstract: To survey Canadian health care professionals about their willingness to offer elective cesarean delivery and to evaluate how their knowledge of obstetric-related pelvic-floor injury influences their practice. A voluntary questionnaire was distributed to health care professionals attending the 58th Annual Meeting of the Society of Obstetricians and Gynaecologists of Canada in 2002. Appropriate statistical analysis was used. One hundred and sixty-two questionnaires were completed. One hundred respondents were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Indeed, when obstetricians were analyzed separately, the same attitude was detected in males and females (data not shown). This finding is in contrast with those of other studies, where male obstetricians were more likely to perform, to agree to, and to believe that a woman has a right to have an elective cesarean section (19,25,26), whereas female obstetricians were more negative toward cesarean delivery (15,16,26), especially when they had already experienced a vaginal delivery (28). It should be acknowledged, however, that our sample of obstetricians could be underpowered to detect a gender difference.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Indeed, when obstetricians were analyzed separately, the same attitude was detected in males and females (data not shown). This finding is in contrast with those of other studies, where male obstetricians were more likely to perform, to agree to, and to believe that a woman has a right to have an elective cesarean section (19,25,26), whereas female obstetricians were more negative toward cesarean delivery (15,16,26), especially when they had already experienced a vaginal delivery (28). It should be acknowledged, however, that our sample of obstetricians could be underpowered to detect a gender difference.…”
Section: Discussioncontrasting
confidence: 95%
“…The strengths of this survey are that all practitioners who attend childbirths in the district of Modena were involved and that the response rate was 94.6 percent, which is much higher than that of previous surveys (25,26). Therefore, we can be confident in the value of the information provided.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Australia, 77.3% of the 1032 obstetricians and 81% of the 258 obstetric trainees would agree to a CSMR in uncomplicated pregnancies [7]). The lowest level of support for a CSMR was among obstetricians from Spain and Canada, where only 15 and 23% of obstetricians respectively would agree to perform a CSMR [5, 8]. In the US, 10.2% of obstetricians reported that they routinely perform CSMRs [9].…”
Section: Maintextmentioning
confidence: 99%
“…Gender differences were noted between male and female obstetricians in their support for CSMRs [8, 12]. In Canada, male obstetricians (34%) were more likely than female obstetricians (16%) to agree to perform a CSMR [8].…”
Section: Maintextmentioning
confidence: 99%